PENGUATAN PEMAHAMAN MODERASI BERAGAMA MELALUI FUN GAME DI KALANGAN PEMUDA RUSUNAWA NGELOM MEGARE KABUPATEN SIDOARJO - Muhammad Syarif Hidayatulloh; Dhofirul Yahya; Millatuz Zahra (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
This service activity aims to provide an understanding of religious moderation and strategies for strengthening and implementing religious moderation through fun games for youth in the Ngelom Megare Taman Sidoarjo flats area. Implementation of this service starts from the planning stage of mentoring activities, seminars on religious moderation and reflection on religious moderation. Through this Fun Game method, they gain independent experience and can understand the implied message about how moderate attitudes should be applied to their environment. The service location was chosen taking into account that the existence of the flat was on the border of the city of Surabaya and the condition of the community was heterogeneous. They have a low understanding of the discourse on religious moderation, especially among young people. So many of them tend to